Study of the influence of the standing time in the electrical conductivity of the saturated soil paste in three soils - Antunes,João (2023)
Abstract The electrical conductivity of the saturated soil paste extract (EC e ) is a reference measurement for soil salinity because it allows comparison among soils regardless of the water content under field conditions. The saturated soil paste is obtained by saturating a soil sample with deionized water, according to a method published about seven decades ago that has been recently updated with the inclusion of an extra standing time of 24 hours. This study analyses the influence of three standing times in the determination of EC e , the saturation percentage (SP), and the electrical conductivity of the soil solution (EC sw ), in three soils with different textures (sand, loam, and silty clay). The results show highly significant differences in EC e and significant differences in EC sw in the sandy soil, when including a standing time of 2 hours compared to no standing time. No significant differences were found when including an additional standing time of 24 hours.